2016
DOI: 10.2147/tcrm.s77788
|View full text |Cite
|
Sign up to set email alerts
|

Combination ledipasvir-sofosbuvir for the treatment of chronic hepatitis C virus infection: a review and clinical perspective

Abstract: Chronic hepatitis C treatment has continued to evolve, and interferon-free, oral treatment with direct-acting antiviral agents is the current standard of care. Recently, a new treatment, which is a combination of two direct-acting antiviral agents, ledipasvir 90 mg (anti-NS5A) and sofosbuvir 400 mg (anti-NS5B), has been approved in the US and the European Union for the treatment of chronic hepatitis C viral infection. In Phase III trials among chronic hepatitis C virus genotype 1 monoinfected (treatment-naïve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Two of the relapsed participants had confirmed NS5A RAS at baseline, however, all 10 had emergent mutations at position 30 and/or 93. The NS5A RAS observed in these studies have previously been attributed to reduced efficacy of LDV in vitro and detected at treatment failure in phase III studies . No emergent NS5B RAS were observed in any of the relapsed participants.…”
Section: Discussionsupporting
confidence: 51%
“…Two of the relapsed participants had confirmed NS5A RAS at baseline, however, all 10 had emergent mutations at position 30 and/or 93. The NS5A RAS observed in these studies have previously been attributed to reduced efficacy of LDV in vitro and detected at treatment failure in phase III studies . No emergent NS5B RAS were observed in any of the relapsed participants.…”
Section: Discussionsupporting
confidence: 51%
“…There are no major studies evaluating the combination Sofosbuvir/Ledipasvir in HCV infected patients with HCV genotype 2 and Ledipasvir has a low activity on HCV genotype [12]. We did not find in the literature a study evaluating the combination sofosbuvir/ledipasvir in kidney transplant patients infected with HCV genotype 2.…”
Section: Combination Sofosbuvir/ledipasvir and Hcv Genotypementioning
confidence: 71%
“…Furthermore, the long-term effects of DAAs remain unclear. Certain DAAs have been associated with the worsening of dyslipidemia (6,7). Although some recent reports have suggested that an SVR by DAA therapy reduces the risk of developing hepatocellular carcinoma (HCC), the role of DAAs in the recurrence of HCC in patients treated for hepatic decompensation remains controversial, and thus, warrants further elucidation and follow-up in the HCC high-risk group (8).…”
Section: Introductionmentioning
confidence: 99%